2006
DOI: 10.1111/j.1440-1754.2006.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory measures in children with obstructive sleep apnoea

Abstract: Aim: To determine the influence of breastfeeding on overweight and obesity in early adolescence. Methods: Data about breastfeeding duration, BMI of children at 14 years, and confounding variables, were collected from an ongoing longitudinal study of a birth cohort of 7776 children in Brisbane. Prevalence of overweight and obesity at 14 years was assessed according to duration of breastfeeding, with logistic regression being used to adjust for the influence of confounders. Results: Data were available for 3698 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 44 publications
3
67
1
12
Order By: Relevance
“…In addition, the levels of CRP returned to non-OSA range after treatment for OSA independent of any significant change in body weight. Another recent study failed to demonstrate significant relationship between OSA and CRP had a study population very similar to that of Kaditis et al 19 The mean age of the subjects was 7.3 years.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, the levels of CRP returned to non-OSA range after treatment for OSA independent of any significant change in body weight. Another recent study failed to demonstrate significant relationship between OSA and CRP had a study population very similar to that of Kaditis et al 19 The mean age of the subjects was 7.3 years.…”
Section: Discussionmentioning
confidence: 88%
“…15 There is accumulating evidence to suggest cardiovascular morbidity also exists in childhood OSA, 2,17 but the few studies on CRP in children with OSA have yielded conflicting results. [18][19][20][21] In a study of 81 children with a mean age of 9.3 years, Tauman et al 20 demonstrated a significant correlation between CRP and the apnea hypopnea index (AHI). Similar correlation between CRP and sleep apnea severity was also documented in a study involving older children with a mean age of 13.7 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P-selectin, C-reactive protein, fibrinogen, interleukin-8, and interferon-␥ levels were found to be higher in children with snoring and/or OSA compared with control subjects. [387][388][389][390][391] In a study of 143 adolescents, mean C-reactive protein level demonstrated a dose-response increase with SDB that was independent of BMI and partially explained by the severity of nocturnal hypoxemia. 91 Whether these mediators predict cardiovascular risk in children and adolescents has yet to be demonstrated.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…8 Other well-studied mechanisms related to obstructive sleep apnea-hypopnea involve endothelial dysfunction and hypoxiarelated expression of proinflammatory cytokines. [12][13][14] A combination of inflammation and vasoconstrictive stimuli largely accounts for the high blood pressure in these patients and for the difficulty to optimally control their values. 15 In the morbid obese population in the study by Avelar et al, 4 body mass index and nocturnal saturation of O 2 account for most of the explained variance of LV mass in addition to systolic blood pressure measured at the office visit.…”
mentioning
confidence: 99%